Incidencia de la densidad poblacional de híbridos de maíz (Zea mays L.) en la infección causada por la mancha de asfalto en la zona de Puebloviejo. - ENGRACIA BARCO, CARLOS JAIRON (2023)
One of the problems today in farmers in their fields is the attack of asphalt stain, it is considered the most problematic fungal disease of corn production in Ecuador and the world. This disease is produced by the synergistic interaction of three fungi: Phyllachora maydis, Monographella maydis and Coniothyrium phyllachorae, which colonize the leaves in a few days and dry them to devour the plant's sugars. Today this disease has become one of the biggest problems for corn growers since it greatly affects their crops where it affects their productions and economic income, thus generating many losses. By means of which the behavior of corn hybrids to the infection caused by the asphalt stain will be evaluated within the plots. The present investigation will be carried out in the rainy season and was carried out in the province of Los Ríos del Cantón Puebloviejo, on the land of Engineer Carlos Vargas Engracia located in the "Las Guijas Pugas 1" compound, between the coordinates longitude W 79° 32'58” and latitude S 1°27'53”. For the development and statistical management of the test, the design called Complete Random Blocks (BCA) with 10 treatments and 3 repetitions was used. For the comparison and evaluation of the generated means, the Tukey test was used at 95% probability. Where the tolerance of each hybrid would be evaluated from the appearance of the disease in each of those hybrids and thus obtaining the appreciated results. The Advanta 9789 hybrid plants planted at 80 cm x 20 cm had larger ears. A higher grain/gopher ratio was calculated in the hybrid Advanta 9789 planted at 70 cm x 15 cm; and 60cm x 20cm. A greater number of ears per plant was found in the Advanta 9789 maize hybrid planted at 80 cm x 20 cm. The highest production was found in the Advanta 9789 hybrid planted at 80 cm x 20 cm, and 70 cm x 15 cm. The highest incidence and severity of the grain spotted disease was found in the Fortaleza maize hybrid planted at 60 x 20 cm.